2016
DOI: 10.1002/btpr.2246
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium‐mediated transformation of Vitis Cv. Monastrell suspension‐cultured cells: Determination of critical parameters

Abstract: Although some works have explored the transformation of differentiated, embryogenic suspension-cultured cells (SCC) to produce transgenic grapevine plants, to our knowledge this is one of the first reports on the efficient transformation of dedifferentiated Vitis vinifera cv Monastrell SCC. This protocol has been developed using the sonication-assisted Agrobacterium-mediated transformation (SAAT) method. A construct harboring the selectable nptII and the eyfp/IV2 marker genes was used in the study and transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…This was shown to be particularly interesting for the production of bioactive compounds (Martínez-Márquez et al, 2015). To improve Agrobacterium-mediated transformation efficiency of dedifferentiated V. vinifera cv Monastrell cells, Chu et al (2016) used the Sonication-Assisted Agrobacteriummediated Transformation (SAAT) method that was previously developed for soybean transformation (Trick and Finer, 1997). This method significantly increases transformation efficiency (Chialva et al, 2016).…”
Section: Agrobacterium-derived Technologiesmentioning
confidence: 99%
“…This was shown to be particularly interesting for the production of bioactive compounds (Martínez-Márquez et al, 2015). To improve Agrobacterium-mediated transformation efficiency of dedifferentiated V. vinifera cv Monastrell cells, Chu et al (2016) used the Sonication-Assisted Agrobacteriummediated Transformation (SAAT) method that was previously developed for soybean transformation (Trick and Finer, 1997). This method significantly increases transformation efficiency (Chialva et al, 2016).…”
Section: Agrobacterium-derived Technologiesmentioning
confidence: 99%
“…Transformation and regeneration of grapevine plants have been achieved via organogenesis [84], embryogenesis [83,93], or from nonembryogenic cell cultures [86,94], demonstrating that grapevine is not recalcitrant to Agrobacterium infection but this approach is time consuming and takes several months to produce transgenic plants suitable for analyses. In some cases, the production of whole transgenic organisms may not be needed if a large number of cells within a plant can be uniformly and consistently transformed.…”
Section: Agroinjection and Agroinfiltrationmentioning
confidence: 99%
“…Sonication-assisted Agrobacterium-mediated transformation (SAAT) was first reported by Trick and Finer [98], who used this technique for the production of transgenic soybean (Glycine max) and Ohio buckeye (Aesculus glabra) plants from SAAT-treated embryogenic cell suspensions. Chu et al [94] recently reported the effect of different times in a sonication bath while infecting dedifferentiated nonembryogenic grapevine suspension cell cultures with A. tumefaciens. Plant tissue damaged by sonication allows the tissue to be much more easily transformed by A. tumefaciens.…”
Section: Sonication-assisted Agrobacterium-mediated Transformation (Smentioning
confidence: 99%